Sense Making and Professional Identity in the Implementation of edTPA. (January 2020) - Cohen, Julie; Hutt, Ethan; Berlin, Rebekah L.; Mathews, Hannah M.; McGraw, Jillian P.; Gottlieb, Jessica
EdTPA is designed to strengthen teacher professionalization and provide a framework for program redesign. However, using a national assessment to shift the content of local programs is challenging because of their inherent organizational complexity. In this article, we focus on this complexity, using a systems lens to analyze edTPA implementation at a large, public university. Employing a mixed-methods case study design, we survey 250 teacher educators and candidates to understand how they interpret the demands of edTPA and how their varied perspectives impact each other. We interview a stratified, purposive subset of participants to explore mechanisms underlying quantitative findings. We find substantial internal variation in edTPA implementation that translates into differential support for candidates. This variation could not be explained by duration of implementation of edTPA. Varied perspectives may stem from distinct perceptions of teacher educators' professional roles and the role they see edTPA playing in teacher professionalization.